Carbon Dynamics During the Formation of Sea Ice at Different Growth Rates - König, Daniela; Miller, Lisa A.; Simpson, Kyle G.; Vagle, Svein (Frontiers in Earth Science, 2018)
Controlled laboratory experiments have shed new light on the potential importance of brine rejection during sea-ice formation for carbon dioxide sequestration in the ocean. We grew ice in an experimental seawater tank (1 m3) under abiotic conditions at three different air temperatures (-40 °C, -25 °C, -15 °C) to determine how different ice growth rates affect the allocation of carbon to ice, water, or air. Carbonate system parameters were determined by discrete sampling of ice cores and water, as well as continuous measurements by multiple sensors deployed mainly in the water phase. A budgetary approach revealed that of the initial total inorganic carbon (TIC) content of the water converted to ice, only 28-29 % was located in the ice phase by the end of the experiments run at the warmest temperature, whereas for the coldest ambient temperature, 46-47 % of the carbon remained in the ice. Exchange with air appeared to be negligible, with the majority of the TIC remaining in the under-ice water (53 -72 %). Along with a good correlation between salinity and TIC in the ice and water samples, these observations highlight the importance of brine drainage to TIC redistribution during ice formation. For experiments without mixing of the under-ice water, the sensor data further suggested stronger stratification, likely related to release of denser brine, and thus potentially larger carbon sequestration for ice grown at a colder temperature and faster growth rate.